Diagnostika difuznih procesov v dojki - Kadivec, Maksimiljan (Radiology and oncology (Ljubljana), 1998)
In mammographic diagnossing we often encounter a dense breast problem. Although the equipment and techniques in mammography have improved considerably in the recent years, the problem of establishing a diagnose in the dense breast which mammography could not detect. Therefore, new methods inthe detection of breast cancer, i.e. ultrasonography, magnetic resonance and radionuclide imaging, have been introduced.
Keywords: Breast neoplasms; Diagnosis; diagnostika; dojke; jedrska magnetna resonanca; Magnetic resonance imaging; Mammography; mamografija; novotvorbe; Ultrasonography, mammary